2011
DOI: 10.1016/j.jfms.2011.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Infection with Cryptococcus Neoformans/Gattii Species Complex and Mycobacterium Avium Affecting the Subcutis and Bone of a Pelvic Limb in a Cat

Abstract: This paper describes a cat with severe localised infections with Cryptococcus neoformans/gattii species complex and Mycobacterium avium affecting the subcutis and underlying fascia and bone of the right pelvic limb. The simultaneous isolation of both pathogens in this patient was unexpected and posed unique issues concerning both diagnosis and clinical management. The aetiopathogenesis of this infection is discussed in relation to aspects of diagnosis and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In cats, disease resembles that caused by M. bovis or M. microti, with cutaneous lesions (especially on the head and limbs) in some cats, osteomyelitis, pulmonary involvement with tachypnea or cough, peripheral and abdominal lymphadenomegaly, and gastrointestinal, liver, splenic, renal, omental, and uncommonly CNS or marrow involvement. 41,42,[44][45][46][47][48][49][50] Gastrointestinal involvement may initially manifest as weight loss despite a good appetite. 41 Dogs with MAC infections often develop marked peripheral or abdominal lymphadenopathy, tonsillar enlargement, hepatosplenomegaly, and/or osteomyelitis.…”
Section: Signs and Their Pathogenesismentioning
confidence: 99%
“…In cats, disease resembles that caused by M. bovis or M. microti, with cutaneous lesions (especially on the head and limbs) in some cats, osteomyelitis, pulmonary involvement with tachypnea or cough, peripheral and abdominal lymphadenomegaly, and gastrointestinal, liver, splenic, renal, omental, and uncommonly CNS or marrow involvement. 41,42,[44][45][46][47][48][49][50] Gastrointestinal involvement may initially manifest as weight loss despite a good appetite. 41 Dogs with MAC infections often develop marked peripheral or abdominal lymphadenopathy, tonsillar enlargement, hepatosplenomegaly, and/or osteomyelitis.…”
Section: Signs and Their Pathogenesismentioning
confidence: 99%
“…12,13,20,29,30 The disease has been reported in cats undergoing chemotherapy or with a concurrent opportunistic infection; hence, a role for immunocompetence cannot be excluded in the pathogenesis of feline cryptococcosis. 24,31…”
Section: Immunitymentioning
confidence: 99%
“…A concurrent infection with Cryptococcus neoformans/Cryptococcus gattii species complex and Mycobacterium avium affecting the subcutis and bone of a pelvic limb in a cat has also been reported. 7 That case also tested negative both for FIV and for FeLV.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies have suggested that cryptococcosis has a higher prevalence or a less favourable outcome in FeLV‐infected or FIV‐infected cats,10 11 but this conclusion has not been found by others5 12–15. Cryptococcal infection has been reported in cats undergoing chemotherapy or with a concurrent opportunistic infection; therefore, immunocompetence could possibly be involved in the pathogenesis of feline cryptococcosis 6 7…”
Section: Discussionmentioning
confidence: 99%